2021
DOI: 10.2298/apt2152111r
|View full text |Cite
|
Sign up to set email alerts
|

Essential oil and ethanolic extract composition from Myrtus nivellei Batt. & Trab. and their biological evaluations

Abstract: This study aims to evaluate the chemical composition and biological effects of an endemic Algerian species Myrtus nivellei belonging to the Myrtaceae family. The aerial parts of the plant were submitted to hydrodistillation and analysed with gas chromatography - mass spectrometry (GC-MS). This oil was yielded 0,75% (w/w). The GC-MS revealed that 1,8 cineole is the most abundant component (53,44%) while other compounds were present in high contents: 2,2,6,7-tetramethyl-10-oxatricyclo [4.3.0.1(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ]. Additionally, there have been reports of linalyl acetate associated antioxidant activity in essential oils of Salvia sclarea , and Myrtus nivellei , across different regions [ 45 , 46 ]. The essential oil attained from Myrtus nivellei demonstrated an IC 50 value of 2.25 mg/mL [ 46 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
See 1 more Smart Citation
“…A study conducted on the lavender essential oils from Lavandula angustifolia demonstrated an IC 50 values of 0.36% ( v / v ) against HaCaT cell line in an MTT assay [ 43 ]. Additionally, there have been reports of linalyl acetate associated antioxidant activity in essential oils of Salvia sclarea , and Myrtus nivellei , across different regions [ 45 , 46 ]. The essential oil attained from Myrtus nivellei demonstrated an IC 50 value of 2.25 mg/mL [ 46 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%
“…Additionally, there have been reports of linalyl acetate associated antioxidant activity in essential oils of Salvia sclarea , and Myrtus nivellei , across different regions [ 45 , 46 ]. The essential oil attained from Myrtus nivellei demonstrated an IC 50 value of 2.25 mg/mL [ 46 ].…”
Section: Biological Activities Of Monoterpenesmentioning
confidence: 99%